A mixed method study of menstrual health in Spain: pain, disorders, and the journey for health - Sánchez-López, Sara; Barrington, Dani Jennifer; Poveda-Bautista, Rocio; Moll-López, Santiago (Frontiers in Public Health, 2025)
IntroductionMenstrual-related symptoms and disorders, particularly dysmenorrhea, significantly impact women's well-being. Dysmenorrhea, marked by painful menstrual cramps, affects up to 95% of women, leading to debilitating symptoms that interfere with daily activities and potentially signal underlying gynecological issues. Despite its prevalence, many women experience inadequate medical support and dismissive healthcare responses.MethodsThis study employed a mixed-method approach, combining quantitative and qualitative survey data to explore Spanish women's experiences with menstrual discomforts and healthcare access. A total of 3,490 participants responded to the survey, which assessed the prevalence of menstrual discomforts, frequency of medical consultations, and perceived quality of gynecological care.ResultsFindings indicate that 70.9% of participants experience menstrual discomforts monthly or most months; despite this, a significant number of women infrequently seek gynecological care, often due to perceived dismissiveness and inadequate medical support. The qualitative analysis reflects shared experiences of pain normalization, misattribution to other conditions, and dissatisfaction with the standard treatment of contraceptive pills without thorough diagnostics. Additionally, the study reveals that in Spain, access to healthcare support for menstrual issues is highly influenced by whether the provider is public or private, demonstrating the impact of socio-economic factors and underscoring a core contributor to health inequity.DiscussionThis study highlights the persistent gender pain gap and the need for a more holistic and empathetic approach in medical practices. The authors' recommendations include incorporating gender training for healthcare professionals and promoting awareness campaigns to encourage medical consultations for menstrual pain. This research aims to improve support systems and healthcare practices, enhancing the quality of life for women in Spain.